Globus pharyngeus a diagnostic challenge for otolaryngologist - Hussain, Tanvir; Patil, Aishan; Copperthwaite, Amy; Fahy, Ronan; Keane, Emma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Globus pharyngeus, also known as globus sensation, can be defined as the sensation of a lump or foreign body in the absence of a mass on examination. The disorder is frequently linked to catarrh, hoarseness, chronic cough and persistent throat clearing. Globus pharyngeus accounts for 4 percent of ENT (ear, nose and throat) referrals. The exact cause of globus pharyngeus is unknown. The presence of lingual tonsil, cricopharyngeal spasm, hiatus hernia, cervical osteophytosis, sinusitis, gastro-oesophageal reflux, goiter post-nasal drip and anxiety have all been shown as associations in the literature. Digestive enzymes and regurgitation of stomach acid are thought to cause persistent inflammation, for example, of the laryngopharynx, which causes symptoms. Reflux has been depicted in 23-68 percent of patients with globus sensation. Notably, some studies claim that asymptomatic control patients have a similar rate. Methods: We presented our audit study of 50 subsets of patients. It was considered that gastro-oesophageal reflux was the reason; however, it cannot explain all the potential causes. Results: Barium swallow was found to be a very key diagnostic tool in this group of patients. Conclusions: Panendoscopy in globus sensation in the throat, looking through the possible causes of globus sensation, current trends and diagnosis as well as methods of treatment.